Complex formation between endogenous toxin bilirubin and polyamidoamine dendrimers: A spectroscopic study - Shcharbin, Dzmitry; Bryszewska, Maria (Biochimica et biophysica acta, 2006)
The effects of 4th and 5th generation cationic, neutral and anionic polyamidoamine (PAMAM) dendrimers on bilirubin absorbance and fluorescence were studied. Cationic and neutral PAMAM dendrimers shifted the bilirubin absorption maximum from 435 to 442–455 nm, increased the peak absorbance 1.5-fold, shifted the bilirubin fluorescence excitation and emission maxima, increased the fluorescence emission several-fold and significantly protected bilirubin against photodestruction. Using double fluorescence titration technique allowed to receive such constant of binding and the number of binding centers at 20 °C: for PAMAM G4 dendrimer, (2.4 ± 1.4) × 10 6 (mol/l) −1 and 0.07 ± 0.012; for PAMAM G4-OH dendrimer, (3.1 ± 1.3) × 10 6 (mol/l) −1 and 0.08 ± 0.014; for PAMAM G5 dendrimer, (7.6 ± 3.6) × 10 6 (mol/l) −1 and 0.09 ± 0.02; and for PAMAM G5-OH dendrimer, (8.5 ± 3.2) × 10 6 (mol/l) −1 and 0.09 ± 0.02. These effects can be explained by the formation of bilirubin–PAMAM dendrimer complexes and the formation of bilirubin monomers from tetramers. The formation of complexes sharply increased bilirubin solubility. We conclude that cationic and neutral PAMAM dendrimers bind bilirubin effectively and suggest that such dendrimers may serve as detoxication agents for hydrophobic endogenous toxins.